Respon Pemberian Berbagai Dosis Bokashi Kulit Buah Kakao Terhadap Pertumbuhan Bibit Kakao (Theobroma cacao L) - Wahyuni, Wahyuni; Arif, Lukman; Kahar, Kahar; Ramadhan, Alif Fhadil (Program Studi Agroteknologi, Fakultas Pertanian Universitas Madako Tolitoli, 2025)
This study aims to determine the response of giving various doses of cocoa pod husk bokashi on the growth of cocoa seedlings (Theobroma cacao L) which was carried out in Kalangkangan Village, Galang District, Tolitoli Regency, Central Sulawesi Province. This study was conducted from April to June 2018. In this study, a completely randomized design (CRD) was used which consisted of 6 (six) levels, namely: P0 = no treatment (control), P1 = cocoa pod husk bokashi fertilizer 50 g / polybag, P2 = cocoa pod husk bokashi fertilizer 100 g / polybag, P3 = cocoa pod husk bokashi fertilizer 150 g / polybag, P4 = cocoa pod husk bokashi fertilizer 200 g / polybag, P5 = cocoa pod husk bokashi fertilizer 250 g / polybag, each treatment was repeated 3 (three) times so that there were 18 polybags per treatment. The results of the study showed that the provision of cocoa pod husk bokashi with a dose of 150 g/polybag, provided results that had a very significant effect on the growth of cocoa plant seedlings, at the age of 13 MST the observation parameters showed an average plant height of 38.67 cm, as well as the observation parameters for the number of leaves at the age of 13 MST on average, namely 18 leaves, providing the best growth of cocoa plant seedlings compared to other treatments, but had no significant effect on stem diameter, root length and root volume.